The Nexus+ approach applied to studies of Impacts, vulnerability and adaptation to climate change in Brazil (Sustainability in Debate, 2020)
This paper aims to present the methodology developed within the Impacts, Vulnerability and Adaptation (IVA) to climate change component of the Fourth National Communication (4CN) of Brazil. The methodological choice of this 4CN involves the application of the nexus+ integrated approach, based on studies of impacts and vulnerabilities for water, energy, food and socio-environmental securities, in the different in the territories of Brazilian biomes, coastal areas and cities. For each of these securities it were identified the observed impacts; analysis of risk conditions; definition and assessments of integrated analysis of key impacts at territorial level; inventory, selection and analysis of adaption options in the context of Nexus+, identifying synergies and trade-offs. This process made possible an integrated assessment among the conditioning risk factors, impacts and interactions among proposed adaptation options.